FIQH MUAMALAH COSMETICS - Nursantri Yanti; Asmuni; Andri Soemitra (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2022)
Fiqh muamalah cosmetics is a study of the law on the use of cosmetics. Although cosmetics are synonymous with women, basically cosmetics are a need for everyone which has a very broad scope. The government through the Majelis Ulama Indonesia is increasingly educating the public regarding halal cosmetics and issuing regulations related to the cosmetic industry to include halal labels as a form of protection for Muslim consumers. Although there have been many halal cosmetics on the market, this is not followed by Muslim awareness to use them. There have been many studies and discussions from previous research on cosmetic fiqh or halal cosmetics. One of them concludes that a person's religion is not a determinant in using halal cosmetics. The purpose of this study was to see the extent of academic studies or discussions about fiqh muamalah cosmetics or halal cosmetics. The research method used is a qualitative approach, namely content analysis of articles from the Google Scholar database. By mapping the themes of previous studies through literature studies. From a search on the Google Scholar database with the keywords "fiqh" and "cosmetics" or "halal cosmetics" in the period 2017 to 2022, 168 articles were found which were then selected into 38 articles that were considered still relevant to the themes discussed. Of the 38 selected articles, they have been grouped into several themes: 1) An overview of Islamic law related to make-up and the use of cosmetics. 2) Halal Labeling and Interest in Cosmetics. 3) Cosmetics business in Islamic Business Ethics.